The System Design for Internship Administration and Pocket Money at PT Pertamina Geothermal Energy - Putri, Yayang Novealita Wahono; Riwajanti, Nur Indah; Eltivia, Nurafni (Journal of Business and Management Review, 2024)
Research Aims: This research aims to design an adequate administration and pocket money internship management system at PT Pertamina Geothermal Energy (PGE). Improvisation will be carried out to prevent human error and increase the processing speed of the internship’s pocket money system. Design/methodology/approach: This research is classified as applied research and was carried out using a Business Process Improvement approach. The procedures include need analysis, planning & design, development, and conclusion. The method used to collect data is by interviewing the Human Capital as the user. Secondary documents and activity forms are obtained through documentation. Research Findings: The system design is based on the concept of Business Process Modelling Notation (BPMN) using Bizagi Modeler. Validation tests by material experts and IT experts are carried out to ensure that the designs have a certain quality and are relevant. The design evaluation system is carried out by involving the Human Capital and Developer Consultant. The level of efficiency can be achieved if the business process model has been designed adequately, and delays in payment can be reduced. Theoretical Contribution/Originality: This research confirms that the problem solved is limited to system design. To obtain results implementation in the problem-solving process at PGE, further research will needed to discuss the system design in advanced Keywords: administration, BPMN, process business, internship, pocket money